Analysis of Efforts to Increase Income Taxes of Social Media Influencers in Endorsement Activities - Fernaldi Anggadha; Haula Rosdiana (Universitas Medan Area, 2020)
Technological developments in the era of globalization have brought changes to marketing techniques, by using social media. Marketing through social media is mostly done by influencers because it is easy to do and earns a fairly large income. The purpose of this study is to analyze the efforts made by the Directorate General of Taxes to increase income tax on social media influencers in endorsement activities. This study adopts the positivism paradigm with qualitative methods. The purpose of this research is descriptive. Primary data sources were obtained through in-depth interviews with selected informants. The results showed that the income of social media influencers or arts workers had great taxation potential. The Directorate General of Taxation seeks to increase income tax receipts for influencers by updating the database, disseminating information and conducting surveillance with law enforcement. The Directorate General of Taxes needs to provide confirmation of the tax provisions for programmatic income so as to provide tax treatment similarities with conventional artist activities and close tax gaps that are widely utilized through online activities.